(untitled) (Journal of Partial Differential Equations, 2004)
" In this paper, Under the assumption that the relaxation time 03b5 is sufficiently small, we prove the existence of the global smooth solution to the Cauchy problem for the Jin-Xin model without any smallness assumption for the initial data. The analysis is based on some a priori estimates which are obtained by the method of characteristic and the maximum principle of first-order quasilinear hyperbolic system."